Dielectric properties of 3-3 flexible composites by infiltration of elastomers into porous ceramic structures using cellulose scaffold. (5th November 2022) - Levy, Ivana K.; Owussu, Francis; Geiger, Thomas; Clemmens, Frank; Nüesch, Frank; Opris, Dorina M.; Negri, R. Martín
Graphical abstract: Highlights: Composites from a pre-sintered structure of BaTiO3, ZnO, CoFe2 O4, BiFeO3 and BiFeO3 -Y, with infiltrated PDMS, are obtained. The electric responses are determined by impedance spectroscopic analysis, dielectric polarization analysis and breakdown-field (EBD ). The responses of infiltrated composites and conventional composites are compared and discussed. The infiltrated composites present larger dielectric constants than the conventional composites. Dielectric losses (tan δ ) remain acceptable low with no significant further decrease in EBD . A remarkable case is BiFeO3 -Y, where the increase of ε s is larger than 600 %, while EBD decreases by a factor of 3. Abstract: Elastomer composites are prepared by infiltrating polydimethylsiloxane (PDMS) into a porous ceramic structure of nanoparticles. This method differs from the conventional approach, where particles are dispersed into the polymer matrix, since here, the polymer is incorporated into a pre-sintered structure of nanoparticles by infiltration under vacuum. Several oxides (CoFe2 O4, ZnO, BaTiO3, BiFeO3, and BiFeO3 doped with yttrium), commonly used for dielectric and piezoelectric devices, were infiltrated by PDMS. The porous 3D structure of nanoparticles is obtained by using cellulose as a scaffold and binder, which is eliminated during the process. Thus, the so-called (3, 3) composites are obtained, where the particles are in direct contact (although immersed in the polymer), at relatively low loading. The dielectric behaviour of the infiltrated and conventional composites is determined by impedance spectroscopy, dielectric polarization analysis, determinations of electric breakdown-field (EBD ), and static dielectric constant ( εs ). The percentage increase of εs from conventional to infiltrated composites is remarkable, reaching for BiFeO3 -Y, an increase of εs and ε′(ω) larger than 600 %, while EBD decreases by a factor of 3.